Risk Factor Analysis of Cryptosporidium sp. Contamination in Dairy Cow Milk in Jember, Indonesia - Sa'bani, Begawan; Hermansyah, Bagus; Sofiana, Kristianningrum Dian; Armiyanti, Yunita; Utami, Wiwien Sugih (Universitas Airlangga, 2024)
This study aimed to determine the factors influencing Cryptosporidium sp. contamination in dairy cow milk in Jember. This study used an observational analytic design with a cross-sectional approach. The number of samples in this study was 30 cow farmers, using a purposive sampling technique. Data sources were obtained from questionnaire interviews, observation sheets, and laboratory examination results of milk samples. Data were then analyzed using univariate, bivariate, and multivariate analysis. Bivariate analysis used the Kruskal-Wallis comparison test, and multivariate analysis used the logistic regression test. The results showed Cryptosporidium sp. contamination in the milk of dairy cows by 6.7%. Most of the cow farmers in Jember had sufficient knowledge (40%), milking hygiene was categorized as sufficient (70%), and equipment sanitation was sufficient (66.7%). The statistical analysis showed no significant relationship between farmers' knowledge and equipment sanitation and Cryptosporidium sp. contamination (p > 0.05). There was a significant relationship between milk hygiene and Cryptosporidium sp. contamination in dairy cow milk in Jember (p < 0.05). In conclusion, milking hygiene was a risk factor affecting Cryptosporidium sp. contamination in dairy cow milk in Jember.